2014
DOI: 10.3844/ajebasp.2014.159.163
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on the One-Parameter Rasch Model

Abstract: The Rasch measurement model improves on traditional test construction by creating tests in which the person's ability is independent of the sample of items used and the norm group used to calibrate the test. This article is an introductory review of the Rasch Model and describes properties of the Item Characteristic Curve (ICC) and discusses the utility of having person ability and item difficulty on a common scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…24,34 Neurodevelopmental ability was computed using item response theory, a psychometric model of a trade-off between test taker's ability and the difficulty of the test. 35 The Rasch model, a 1-parameter logistic model to determine an infant's ability based on their responses to multiple test items, was used. 35 A standardized (mean zero, unit SD) score was determined for each infant for each MDAT developmental domain and an overall developmental score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,34 Neurodevelopmental ability was computed using item response theory, a psychometric model of a trade-off between test taker's ability and the difficulty of the test. 35 The Rasch model, a 1-parameter logistic model to determine an infant's ability based on their responses to multiple test items, was used. 35 A standardized (mean zero, unit SD) score was determined for each infant for each MDAT developmental domain and an overall developmental score.…”
Section: Discussionmentioning
confidence: 99%
“…35 The Rasch model, a 1-parameter logistic model to determine an infant's ability based on their responses to multiple test items, was used. 35 A standardized (mean zero, unit SD) score was determined for each infant for each MDAT developmental domain and an overall developmental score. This allowed ranking of individuals by neurodevelopmental ability within the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Third, calibration scaling analysis. Finally, the dimensionality is also used to verify both content and construct validity [26,19,42,17,38]. Table 2 showed that the Item Polarity and Item Fit Analysis for Economic Values Scale.…”
Section: Validity and Reliability Using Rasch Modelmentioning
confidence: 99%
“…Rasch developed a special model, to estimate the abilities of individuals through their responses on the test items (McCamey, 2014). Rasch model helps to predict probability of the correct answer on a test based on an estimate items two variables which are difficulty of item and ability of the individual through joint continuity between them (De Battisti, Salini, & Crescentini , 2004).…”
Section: Rasch Modelmentioning
confidence: 99%